KONSEP OTOMATISASI PENGATURAN PARKING STAND DALAM MENINGKATKAN KINERJA AMC DI BANDAR UDARA INTERNASIONAL SAM RATULANGI MANADO - Rama Putra Hadisutjipto; Kukuh Tri Prasetyo; Setyo Hariadi (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The growth in the world of aviation that continue to move forward provide us with convenience in using air transportation and working in the world of aviation, one example of which is AOCC. AOCC is a combination of all Stakeholders with the aim of facilitating communication between units in carrying out their duties. This system makes it easier for AMC personnel as an airside operational unit to provide information about parking stands to other units. The research method used is a quantitative method of data collection by means of field observations, interviews and questionnaires. The population in this study were 31 AMC personnel and AOCC unit personnel at Sam Ratulangi International Airport, Manado. The samples used by the researchers were all AMS and AOCC personnel, totaling 31 respondents. The results of this study are based on data obtained from the field which is then processed using the SPSS 21 intrument method with Pearson correlation and manual calculations to find the final results. The final result obtained from this research is that according to the data that has been processed by the researcher using the SPSS 21 intrument, the data shows that the automation concept can improve the performance of AMC personnel at Sam Ratulangi International Airport, Manado. This is evidenced by the test we have using SPSS 21 which shows that the value of R count > from the R table and the value of the Pearson correlation is positive which indicates the concept of automation and the performance of AMC personnel has a connection.